High-grain diet feeding altered the composition and functions of the rumen bacterial community and caused the damage to the laminar tissues of goats - R.Y. Zhang; W. Jin; P.F. Feng; J.H. Liu; S.Y. Mao (Animal, 2018)
In the current intensive production system, ruminants are often fed high-grain (HG) diets. However, this feeding pattern often causes rumen metabolic disorders and may further trigger laminitis, the exact mechanism is not clear. This study investigated the effect of HG diet feeding on fermentative and microbial changes in the rumen and on the expression of pro-inflammatory cytokines and matrix metalloproteinases (MMPs) in the lamellar tissue. In all, 12 male goats were fed a hay diet (0% grain; n=6) or an HG diet (56.5% grain; n=6). On day 50 of treatment, samples of blood, rumen content, and lamellar tissue of hooves of goats were collected. The data showed that compared with the hay group, HG-fed goats had lower (P<0.05) rumen pH but higher (P<0.05) total volatile fatty acids and lactate in the rumen and higher (P<0.05) lipopolysaccharide (LPS) levels in the rumen and blood. HG diet feeding altered the composition of rumen bacterial community, and correspondingly, the results suggested that their functions in the HG group were also altered. HG diet feeding increased (P<0.05) the expression of interleukin-1β, interleukin-6, tumour necrosis factor-α and MMP-2 mRNA in the lamellar tissues compared with the hay group. Correlation analysis indicated that the expression of pro-inflammatory cytokines were positively correlated with MMP-2 expression in lamellar tissues. Overall, these results revealed that HG feeding altered the patterns of rumen fermentation and the composition and functions of rumen bacterial community, and lead to higher levels of LPS in the peripheral blood, and further activated the inflammatory response in lamellar tissues, which may progress to the level of laminar damage.